Offspring dispersal ability covaries with nest-site choice. (24th November 2018) - Delaney, David M; Janzen, Fredric J
Abstract : Nesting strategy shifts with offspring dispersal ability. In snapping turtles, larger offspring have higher survival than smaller offspring when dispersing long distances. Mothers that produce better dispersing offspring nest farther from water where nest predation risk is lower. Mothers that produce poorer dispersing offspring are constrained to nest closer to water so offspring can successfully disperse if they aren't eaten first. Thus, accounting for offspring dispersal ability increases offspring survival and maternal fitness. Abstract: Optimal maternal investment is often a tradeoff between conflicting pressures and varies depending upon environmental context and intrinsic female traits. Yet, offspring phenotype might also interact with such factors to influence investment. In aquatic turtles, terrestrial nests constructed farther from shore often have higher survival because nest predators tend to forage along environmental edges. However, offspring from eggs deposited farther inland must migrate farther to water upon emergence. We released hatchling common snapping turtles ( Chelydra serpentina ) at varying distances from a drift fence and monitored survival during overland dispersal. Survival decreased with dispersal distance and no selection on body size was evident for hatchlings dispersing from short- or intermediate-distances. However, survival increased with body size for hatchlings dispersing from the longest distance. Moreover, females producing larger and better dispersing offspring oviposited farther from water than females that produced smaller and poorer dispersing offspring. This conditional (on offspring body size) tradeoff suggests female investment can be sensitive to offspring phenotype and that such covariation between nest-site choice and offspring dispersal ability can maximize offspring survival and, thus, maternal fitness. Future work that considers the role of offspring performance on maternal behavior will elucidate an underappreciated influence of investment strategies.